In vivo regulation of the uvrA gene: role of the "-10" and "-35" promoter regions. - Backendorf, C (1983)
The effect of increasing deletions in the uvrA promoter region on the transcriptional efficiency was quantitatively analysed by fusion to the galK structural gene. A physical analysis of uvrA messenger RNA synthesis from the different deletion plasmids was performed using the S1 mapping technique. Both methods indicate that the uvrA "-10" promoter sequence is sufficient to trigger uvrA transcription. Although not essential, the "-35" region, which is overlapping with the LexA binding site, is shown to have an enhancing function, as the exposure of this region after SOS induction results in a 3- to 4-fold increase in uvrA transcription. A model is presented which accounts both for the observed basal and induced expression of the uvrA gene on a molecular level.